Use of Monoterpenes as Potential Therapeutics in Diabetes Mellitus: A Prospective Review - Leonardo da Rocha Sousa; Nildomar Ribeiro Viana; Angélica Gomes Coêlho; Celma de Oliveira Barbosa; Débora Santos Lula Barros; Maria do Carmo de Carvalho e Martins; Ricardo Martins Ramos; Daniel Dias Rufino Arcanjo (Advances in Pharmacological and Pharmaceutical Sciences)
Monoterpenes are secondary metabolites of plants belonging to the terpenoid class of natural products. They are the most abundant components of essential oils that are generally considered to have various pharmacological properties. These compounds are reported to have antidiabetic effects in recent years. Due to nature’s complex biosynthetic machinery, they also exhibit a reasonable degree of structural complexity/diversity for further analysis in structure-activity studies. Therefore, monoterpenes as antidiabetic agents have been investigated by recent in vitro and in vivo studies extensively reported in the scientific literature and claimed by patent documents. The purpose of this survey is to provide a comprehensive and prospective review concerning the potential applications of monoterpenes in the treatment of diabetes. The data for this research were collected through the specialized databases PubMed, Scopus, Web of Science, and ScienceDirect between the years 2014 and 2022, as well as the patent databases EPO, WIPO, and USPTO. The research used 76 articles published in the leading journals in the field. The main effect observed was the antidiabetic activity of monoterpenes. This review showed that monoterpenes can be considered promising agents for prevention and/or treatment of diabetes as well as have a marked pharmaceutical potential for the development of bioproducts for therapeutics applications.